Review of the genus Haba Semenov, 1954 (Hymenoptera Chrysididae) with the key to species - Strumia, Franco (Zootaxa, 2016)
Four species of the genus Haba are reviewed. New combination is proposed for Haba colonialis (Mocsáry, 1911), comb. nov. (from Holopyga). The synonymy between Holopyga colonialis and Holopyga beaumonti Balthasar, 1953 is not supported. Key to the species is given.